Evaluation of alternate crops and intercropping systems to bt cotton (Gossypium spp.) in rainfed alfisols - P.V.RAO, T. SONIYA, G. VEERANNA, P. RAGHU RAMI REDDY and (The Journal of Research, PJTSAU, 2017)
India is endorsed with variety of soils ranging from poor Coastal sands to highly fertile deltaic alluviums. Alfisols denote the second largest soil groups of the country covering an area of 200,000 sq. miles. The soils are found in the states of Andhra Pradesh, Karnataka, Tamilnadu, Southern Maharashtra, Orissa and Chotanagpur plateau of Jharkhand (agri.coop.nic.in).